Digital Solutions in the Inclusive Education of Children with Autism Spectrum Disorders - E.N. Soldatenkova; I.V. Blinova (Moscow State University of Psychology and Education, 2021)
The article describes assistive technologies - mobile applications «I Read Without Mom» and «My Album», developed to educate children with autism spectrum disorders. Presented applications are designed on the basis of the traditions of national scientific knowledge and aimed to help in solving the problem of including children with autism spectrum disorders in the educational environment. Discussed applications can help to organize work with children, can become a functional prosthesis in the absence of speech at the initial stage of working with the child (one of the applications can be used as a communicator). Applications goals include: pointing out and development of the child's «I-action», development of a «concept area comprehension», development of oral speech, in non-speaking preschool children this is implemented by restructuring the way the impaired function is realized. Mobile applications which are focused on a generalized method of pedagogical action developed as a template that allows to use it variably, personifying the educational trajectory not only in working with ASD children. The applications are supplemented with methodological recommendations for professionals and parents.